Digital radiography of interproximal bone loss: validity of different filters - Eickholz, Peter; Rieß, Thomas; Lenhard, Markus; Haßfeld, Stefan; Staehle, Hans Jörg (Journal of clinical periodontology, 1999)
The aim of the present study was to compare linear measurements of interproximal bone loss on digitized radiographic images after application of different filters to the gold standard of intrasurgical measurements.
Elektronische Reproduktion der Druck-Ausgabe
First published: 20 October 2003
Gesehen am 24.02.2021